PENGARUH TOTAL QUALITY MANAGEMENT DAN KOMITMEN LEADERSHIP TERHADAP KINERJA KARYAWAN PADA PT. TUAH SEJATI KRUENG JREUU INDRAPURI ACEH BESAR - Fadli Armanda (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2024)
This study aims to test and analyze the influence of TQM on employee performance at PT. Tuah Sejati, to test and analyze the influence of leadership commitment on employee performance at PT. Tuah Sejati and To test and analyze the influence of TQM and leadership commitment on employee performance at PT. Tuah Sejati. Data analysis used in this study is the multiple linear regression analysis method. The sample in this study was 22 employees of PT. Tuah Sejati. The results of the study indicate that Total Quality Management has no effect on employee performance at PT. Tuah Sejati. This can be seen in the results of data processing where the t count value is -0.022 ≥ t table 2.093. Leadership commitment has a positive effect on employee performance at PT. Tuah Sejati. This can be seen in the results of data processing where the t count value is 2.880 ≥ t table 2.093. Total Quality Management and Leadership Commitment have an effect on employee performance at PT. Tuah Sejati. This can be seen in the data processing results, where the calculated t value is 6.855 ≥ t table 3.522.